Marketing public relations for new political parties: An analytical study of the communication activities of the new political parties on Facebook - M.Leith Sabbar Jaber (lark, 2020)
Specialists in the field of politics and media clearly indicate the impossibility of the public relations function being absent from the work of political parties, being the mirror reflecting their party programs and policies as well as “their constant endeavor to establish relations of affection, trust and belonging between the various parties involved in the political process, and this will not be achieved unless it is won Public trust and knowledge of its orientations and this depends on the function of public relations in the organizational structure of the political party, this research tries to clarify the reality of the work of marketing public relations in the new Iraqi political parties in addition to knowing the communication activities that they employed in their pages on the website (Facebook) to deliver the party’s message and introduce its policy and programs The electoral results of the research: The results of the research revealed the interest of those in charge of the pages of political parties in the identifying elements of the shape of the page. Main, to communicate its activities, programs, visions and orientations without paying any attention to employing people Other electronic sites, research recommendations: The researcher recommends the need to pay attention to the work of public relations and give it a prominent place in organizing the political party, as it is the woman who reflects its electoral program and the link between it and the public. Those in charge of the party’s pages on the Facebook site should pay attention to employing other languages ​​aimed at the public. And also, "the necessity to seek the expertise and advice of public relations specialists in how to prepare programs and campaigns that form a positive mental image for the political party and reflect the policy of its programs to the public."